Given:" "x^2+3x-10=0.......................(1)
color(blue)("Determine "y_("intercept"))
Read directly from equation (1)
color(blue)(y_("intercept")=-10)
color(brown)("'~~~~~~~~~~~~~ Tip! ~~~~~~~~~~~~~~~~~~~~")
color(green)("As the equation is already in the form ")
color(green)(y=a(x^2+b/a x) + c)
color(green)("In this case "a=1)
color(green)(x_("vertex")=(-1/2)xxb/a = -3/2)
color(brown)("'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~")
color(blue)("Step 1")
Write equation (1) as (x^2+3x)-10=0
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Step 2")
Add the adjustment constant k
(x^2+3x)-10+k=0
'~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Step 3")
Move the power from x^2 to outside the bracket
(x+3x)^2-10+k=0
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Step 3")
Remove the x" from "3x
(x+3)^2-10+k=0
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Step 4")
Multiply the 3 inside the bracket by 1/2
(x+3/2)^2-10+k=0
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
color(blue)("Step 4")
If we multiply out the bracket we end up with an additional term to those in the original equation. That term is (3/2)^2 derived from (?+3/2)(?+3/2)=(3/2)^2. This term must be removed which is achieved by making k=-(3/2)^2
So now we have
color(brown)((x+3/2)^2-10+k=0)color(green)(->(x+3/2)^2-10-(3/2)^2=0)
color(blue)("Completing the square "->)color(magenta)( (x+3/2)^2-49/4=0)......................(2)
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
" "color(blue)("Vertex" -> (x,y)->(-3/2,-49/4))
From equation (2)
(x+3/2)^2=49/4
Square rooting both sides
x+3/2= +-sqrt(49)/sqrt(4)
color(blue)(x_("intercepts")=-3/2+-7/2 = -5 or +2)#